Simulation of failure of air plasma sprayed thermal barrier coating due to interfacial and bulk cracks using surface-based cohesive interaction and extended finite element method - Kyaw, S.T.; Jones, I.A.; Hyde, T.H. (SAGE, 2016)
The present paper describes a method of predicting the failure of a thermal barrier coating system due to interfacial cracks and cracks within bulk coatings. The interfacial crack is modelled by applying cohesive interfaces where the thermally grown oxide is bonded to the ceramic thermal barrier coating. Initiation and propagation of arbitrary cracks within coatings are modelled using the extended finite element method. Two sets of parametric studies were carried out, concentrating on the effect of thickness of the oxide layer and that of initial cracks within the ceramic coating on the growth of coating cracks and the subsequent failures. These studies have shown that a thicker oxide layer creates higher tensile residual stresses during cooling from high temperature, leading to longer coating cracks. Initial cracks parallel to the oxide interface accelerate coating spallation and simulation of this process is presented in this paper. By contrast, segmented cracks prevent growth of parallel cracks which can lead to spallation.